Media ownership and news coverage: A critical appraisal of private media organisation - Amos, Victor; Joseph, Ayodele Babatunde (Journal of Language and Pragmatics Studies, 2023)
Information is central to all forms of human activity no matter the field, be it medicine, agriculture, tourism or engineering. There is the need for exchange of information to ensure completion of tasks. Inefficiency will be the results, where this exchange of information is slow or there is a break down. For this reason, information is regarded as a vital resource that needs to be properly developed, because it has boomerang effect on society. News media ownership assumes different characteristics depending on whether and when it is profitable or politically interesting to own media. When investing in news production is economically beneficial, it typically attracts corporate owners aiming to maximize profit on the public stock market. When investments in news production are politically beneficial, it typically attracts industry, military, or partisan ownership. When news media ownership is not economically beneficial, as has been the development in Western media systems in recent years, it attracts a variety of owners with different motives.